Early hominins in north-west Europe: A punctuated long chronology?. (15th June 2018) - Hosfield, Rob; Cole, James
Abstract: In light of changing views regarding the identity and evolutionary positions of Europe's Lower Palaeolithic hominins, a re-consideration of the hominin occupation of north-west Europe from c . 1 million years ago (mya) to c . 400 thousand years ago (kya) is timely. A change in the scale and character of the overall European Palaeolithic record around c . 800–600 kya has been well documented and argued over since the mid-1990s. Hominin expansion into the European north-west, potentially from southern Europe, Africa or south-western Asia, has been linked to the introduction of a new lithic technology in the form of the biface. We evaluate three potential drivers for this northern range expansion: changing palaeo-climatic conditions, the emergence of an essentially modern human life history, and greater hominin behavioural plasticity. Our evaluation suggests no major changes in these three factors during the c . 800–600 kya period other than enhanced behavioural plasticity suggested by the appearance of the biface. We offer here a model of hominin occupation for north-west Europe termed the 'punctuated long chronology' and suggest that the major changes in the European Lower Palaeolithic record that occur at a species-wide level may post-date, rather than precede, the Anglian Glaciation (marine isotope stage (MIS) 12). Highlights: European Lower Palaeolithic includes key shift in hominin distribution. Shift from below 45° north to broader range including higher latitudes. Changes in palaeoenvironmental conditions or hominin life history not key factors. Increasingly plastic behaviour may have enabled hominin range expansion.